“DOORS” IN A DOLL’S HOUSE AND IBSEN’S THOUGHT OF FREEDOM - AFM, MOSHIUR RAHMAN (Innovare Journal of Social Sciences, 2023)
The present study aims at exploring the representation of “Doors” in different places of the whole play. Based on the objectives and the nature of the study, the qualitative research method has been used to conduct the research. Content analyses have been applied to analyze the elicited data for the study. The study has explored that a very significant word “Door” connected to the title of the study was used to signify a number of notable points including welcoming anybody, keeping something secret, forbidding somebody to enter somewhere, forcing someone to stay, getting rid of something boring, something wanted coming, switching concentration, tension and stress regarding the arrival of something unwanted, and opening up a new horizon of freedom. The “Door” slammed by Nora at the very end of A Doll’s House indicates the closing of the door of dependence and opening up a new door, the door of true individuality, learning, maturity, and freedom. Finally, the true thought of Ibsen is found through his search for truth and individuality regardless gender and freedom. Hence, it can be said that the present study will be a great source of literary information for the future researcher in the connected fields.